ANALISIS SEKTOR POTENSIAL DI KABUPATEN KLUNGKUNG - Widiantara, I Nengah Jaya; Budhi, Made Kembar Sri (Buletin Studi Ekonomi; VOL.24.NO.1.FEBRUARI 2019DO - 10.24843/BSE.2019.v24.i01.p03, 2019)
Abstract: Analysis of Potential Sectors in Klungkung Regency. Klungkung Regency as one of the regions in Bali Province has a considerable opportunity in developing the potential of the region it has in order to support the economic development of Klungkung Regency. This study aims to analyze the potential sectors in Klungkung Regency in terms of Gross Regional Domestic Product. The data used secondary data. This study used GRDP data from the period 20122016. The analysis technique used are Location Quotients (LQ) analysis, Growth Ratio Model (MRP) and Overlay. The results show that the potential sectors in Klungkung Regency during the 2012-2016 period are 4 sectors, namely (1) manufacturing industry sector ; (2) information and communication; (3) health services and social activities; and (4) other services. The results of the analysis which show that for these four sectors have a positive growth rate and make a large contribution in the GRDP of Klungkung Regency. The government should make several policies to improve  the performance of these sectors by providing stimuli in the form of capital. With the existence of  capital, in this case such as credit loans and subsidies so that later  sectors  that have not this  potential can develop into a potential sector.